PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN. (UPT Pengelolaan Sumber daya Air Tumpang) - Asmar Makruf; Afi Rachmat Slamet; M. Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT This study aims to determine the effect of leadership, motivation and work discipline on employee performance in UPT overlapping water resources management Tumpang. There are 51 employees in this organization so in this study the sample was taken using the census method because respondents were all employees in the organization. For statistical analysis tools use multiple linear regression analysis. From the statistical results obtained using multiple regression analysts that leadership has a calculated t value greater than t table (2,011) of 2.947, motivation of 3.034, work discipline of 3.342 and the results of the F test showed 16.636. This shows that leadership has a significant positive effect on performance, motivation has a significant positive effect on performance, work discipline has a significant positive effect on performance while simultaneously leadership, motivation and work discipline have a significant positive effect on the performance of UPT overlapping water resources management Tumpang employees. Key words: leadership, motivation, discipline of work and the employee performance.